MENUJU PEMILIHAN UMUM 2024: STRATEGI OPTIMALISASI INFORMASI TAHAPAN PEMILU DI KOMISI PEMILIHAN UMUM KABUPATEN BANTUL - Muhammad Rifa’at Adiakarti Farid; Eka Anisa Sari; Yudha Wirawanda; Fajar Junaedi (Nusantara Hasana Journal, 2024)
This research is to observe the flow of optimization and use social media of the General Election Commission (KPU) Bantul Regency to welcome the 2024 election and its effect on society. This study also examines the effect of branding as an election organizer that can be recognized by the public using descriptive qualitative methods. The results of this study, the Bantul Election Commission increases media literacy ahead of the democratic party as a way of branding election organizers by maximizing digital tools including Websites, Instagram, Facebook and Youtube in an effort to  increasing voter participation and public trust.